Physics and politics in revolutionary Russia - Josephson, Paul R. (University of California Press, 1991)
Aided by personal documents and institutional archives that were closed for decades, this book recounts the development of physics--or, more aptly, science under stress--in Soviet Russia up to World War II. Focusing on Leningrad, center of Soviet physics until the late 1930s, Josephson discusses the impact of scientific, cultural, and political revolution on physicists' research and professional aspirations. Political and social revolution in Russia threatened to confound the scientific revolution. Physicists eager to investigate new concepts of space, energy, light, and motion were forced to accommodate dialectical materialism and subordinate their interests to those of the state. They ultimately faced Stalinist purges and the shift of physics leadership to Moscow. This account of scientists cut off from their Western colleagues reveals a little-known part of the history of modern physics.
Keywords: Physics -- Soviet Union -- History -- 20th century.; Physics -- Research -- Soviet Union -- History.; Physics -- Political aspects -- Soviet Union -- History.; Science and state -- Soviet Union -- History -- 20th century.; Science -- Political aspects -- Soviet Union -- History.; Physique -- URSS -- Histoire -- 20e siècle.; Physique -- Recherche -- URSS -- Histoire.; Physique -- Aspect politique -- URSS -- Histoire.; Politique scientifique et technique -- URSS -- Histoire -- 20e siècle.; Sciences -- Aspect politique -- URSS -- Histoire.; SCIENCE -- Philosophy & Social Aspects.; SCIENCE / General; Physics; Physics -- Research; Science and state; Science -- Political aspects; Soviet Union; Russische Revolutie.; Natuurkunde.; Sovjet-Unie.; Physics.; Physical Sciences & Mathematics.; Physics - General.; 1900-1999; History